The relationship of economic policy uncertainty with the stock market index and the exchange rate: The case of Russia - Hakan Yıldırım; Meltem Ince-Yenilmez (Journal of New Economy)
National economic policy uncertainty is a determinant of stock market volatility, decreased investor confidence, and macroeconomic instability. The study aims to examine the interaction between Russia’s Economic Policy Uncertainty Index (REPU), the Moscow Stock Exchange RTS Index (RTSI) and the exchange rate of US dollar to Russian ruble. Methodologically, the analysis relies on the theories of financial markets and the concept of economic uncertainty. The causality is investigated using the Granger causality test. The data is the monthly indices and exchange rates for January 1996 – July 2024. The findings indicate that there is no statistically significant causality from the REPU to the RTSI, which suggests that the direct impact of economic policy uncertainty news on stock prices is limited. However, a significant causation is established between the REPU and the exchange rate, indicating that policy uncertainty causes currency depreciation. This evidences that economic policy uncertainty plays an important role in exchange rate fluctuations. The insights derived from the study could help policymakers and investors assess issues related to financial stability and exchange rate risks. In future, the study could be extended to examine other macroeconomic indicators and external shocks influencing financial markets.